1993
DOI: 10.1507/endocrj.40.99
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adrenodemedullation on In Vivo Insulin-Stimulated Glucose Utilization in Relation to Glycolysis in Rat Peripheral Tissue.

Abstract: Abstract. The effect of adrenodemedullation (ADMX) on insulin action was examined in anesthetized rats by means of a three-step euglycemic clamp procedure (insulin infusion rate: 0, 6.0 and 30.0 mU•kgBW-1•min-1) combined with a microdialysis technique in skeletal muscle and adipose tissue. The dialysate lactate levels in the above tissues increased in parallel with the plasma lactate levels during the sequential euglycemic clamp. In the euglycemic clamp, the glucose infusion rate (GIR) was significantly (P<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Metabolic clearance rate for glucose (MCR, ml´kg ±1´m in ±1 ) was then obtained from GDR divided by the corresponding blood glucose concentration. The GDR and the MCR from 60 to 90 min for the euglycaemic clamp procedure were regarded as indices of insulin action in peripheral tissues, since a plateau glucose infusion rate was achieved during this time, as reported previously [14,15]. In a final group of rats N-monomethyl-l-arginine (l-NMMA, Calbiochem-Novabiochem, Nottingham, England) was infused (1 mg × kg ±1 × min ±1 ) in diabetic rats together with C peptide I (0.05 nmol × kg ±1 × min ±1 ) during low-dose insulin infusion according to the same protocol as described above.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…Metabolic clearance rate for glucose (MCR, ml´kg ±1´m in ±1 ) was then obtained from GDR divided by the corresponding blood glucose concentration. The GDR and the MCR from 60 to 90 min for the euglycaemic clamp procedure were regarded as indices of insulin action in peripheral tissues, since a plateau glucose infusion rate was achieved during this time, as reported previously [14,15]. In a final group of rats N-monomethyl-l-arginine (l-NMMA, Calbiochem-Novabiochem, Nottingham, England) was infused (1 mg × kg ±1 × min ±1 ) in diabetic rats together with C peptide I (0.05 nmol × kg ±1 × min ±1 ) during low-dose insulin infusion according to the same protocol as described above.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…During the microdialysis, the probe was connected to a microinfusion pump (Carnegie Medicin, Sweden) and continuously perfused at 1 pl/min with Krebs-Henseleit bicarbonate (KHB) buffer (except that the Ca2+ concentration was reduced from 5 to 2.5mEqll). Our recent study (24) has shown that the in vim recovery of lactate (dialysate concentrations vs medium concentration x 100) is 60.8 + 1.2% at a perfusate flow rate of 1 yllmin and that the recovery remains constant at the lactate concentration of up to at least 30.00 mgldl. The dialysate was collected at the outlet of the probe every 15 min for analysis of lactate following a stabilization period of 60 min.…”
Section: Methodsmentioning
confidence: 94%
“…We hypothesize that one of the responsible mechanisms for these conflicting data could be due to increased glycolysis in peripheral tissues since increased lactate production was found during hyperinsulinemic euglycemic clamp (3) and peripheral tissues were major contributors to increased insulin action by physical training (7). Recently, we have developed a sequential eugiycemic clamp in combination with a microdialysis technique in skeletal muscle and adipose tissue in the rat (24). Using this technique, we have shown that the dialysate insulin-stimulated lactate level in the above mentioned tissues is mainly a reflection of lactate formation and changes in parallel with glucose infusion rate (GIR) during the euglycemic clamp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro recovery rates of 3-OHBA and lactate (dialysate concentration vs. medium concentration x 100) were measured as previously reported [10,14] and were then 60.8 ± 3.4% and 56.6 ± 1.1%, respectively, at a perfusate flow rate of 1.4 ,ul/min. Probes were placed in media containing varying concentrations of 3-OHBA (20 to 800 4umol/l) and lactate (0.3 to 3.0 mmol/l) and were continuously perfused with KHB at 1.4 4u1/min.…”
Section: Experimental Protocolmentioning
confidence: 96%